PERBANDINGAN BERAS RAGI MERAH DAN SIMVASTATIN DALAM MENURUNKAN PROFIL LIPID : EVIDENCE-BASED CASE REPORT - Dian Sarah Mutiara Dian Sarah Mutiara; Diana Sunardi (Perhimpunan Dokter Gizi Klinik Indonesia, 2021)
Abstract Background: Dyslipidemia is major risk factor of non-communicable disease and nutraceutical like red yeast rice (RYR) may be helpful as alternative to lowering lipid profile in dyslipidemia. Research objectives: This literature is to critically analyze the comparison RYR and simvastatin in lowering lipid profile. Methods: A search for relevant literatures in PubMed, Scopus, Cochrane, and Science Direct was conducted. We assessing the relevancy and eligibility of the literatures. Three literatures were selected and critically appraised. Results: There were no significant different between RYR and statin group for triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), especially the total cholesterol (TC) and the low-density lipoprotein-cholesterol (LDL-C) level. Red yeast rice (RYR) show less fatigue side effect than statin. Conclusions: Nutraceutical like RYR can be an alternative to lowering lipid profile especially TC level and LDL-C level and solution for patients who experience statin-associated myalgia. Keywords: red yeast rice, monacolin K, simvastatin, lipid profile